PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM SUBSEKTOR INDUSTRIAL GOODS PADA SEKTOR INDUSTRI DI INDONESIA - Maeyzhal, Fanya; Zaretta, Bara; Kurniawan, Rudi; Oktavia, Vicky (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the impact of diversified financial metrics specifically profitability (ROA, NPM, EPS), liquidity (CR), solvency (DER), and market valuation (PBV) on stock return. Utilizing a sample of 24 firms within the Indonesian Stock Exchange's (IDX) industrial goods subsector from 2020 to 2024, the study employed a purposive sampling approach. Analytical results derived from panel data regression via the Common Effect Model (CEM) framework indicate that NPM, PBV, and CR serve as significant determinants of stock return. In contrast, EPS, ROA, and DER failed to demonstrate a meaningful influence. Furthermore, the Adjusted R-squared value is 0.1066, this indicates that the independent variables in this model are able to represent 10.66% of the dependent variable.